THE BEST INTERESTS OF THE CHILD FROM AN ADULT PERSPECTIVE (A Case Study on Child Marriage Dispensation Cases at the Sukadana Religious Court) - Fathoni, Muhammad Nur; Oktora, Nency Dela; Wijayati, Mufliha (istinbath, 2024)
This study examines how the child's best interests principle is applied in child marriage dispensation cases at the Sukadana Religious Court, emphasizing the contrasting viewpoints of applicants (parents or guardians) and judges. This topic is significant due to the high prevalence of child marriages at the Sukadana Religious Court, which frequently leads to various adverse effects on children's development. This research employs a qualitative approach combining normative and empirical methods, utilizing a case study framework. It includes an analysis of decisions from the Sukadana Religious Court, in-depth interviews with judges, and a review of case applicants. The results reveal that applicants and judges have yet to apply the child's best interests principle fully. Second, the applicants tend to focus on quick solutions to social, moral, or cultural pressures, such as out-of-wedlock pregnancies, premarital sexual relations, or concerns about family shame. Third, judges adopt a normative approach by assessing the child and their partner's physical, psychological, and financial readiness. However, they often prioritize solutions to the urgent situations presented by the applicants. The study concludes that strengthening the implementation of the child's best interests requires stricter regulations in decision-making, offering pre-marriage education and awareness programs on children's rights, and improving judges' competencies. This study recommends collaboration between the courts, educational institutions, and community organizations to strengthen public understanding of the child's best interests as the primary principle in child protection.